Extracorporeal membrane oxygenation-supported one-stop surgery for transcatheter aortic valve replacement and percutaneous coronary intervention in high-risk complex coronary artery and aortic valvular disease: a case report - Zhang, Zhihan; Wang, Dongsheng; Yu, Yanan; Du, Beibei; Zhang, Zhongfan; Liu, Guohui (Frontiers in Cardiovascular Medicine, 2025)
Aortic stenosis (AS) is frequently associated with coronary artery disease (CAD), particularly in high-risk patients for whom treatment strategies lack standardized clinical guidelines. We report a case of a patient with severe AS and high-risk CAD, leading to significant heart failure, for whom surgical aortic valve replacement and coronary artery bypass grafting were unsuitable because of very high risk of morbidity and mortality. The patient underwent a one-stop procedure combining extracorporeal membrane oxygenation (ECMO)-assisted transcatheter aortic valve replacement (TAVR) and percutaneous coronary intervention (PCI). During the procedure, the patient first received preventive veno-arterial ECMO placement, successfully underwent PCI on the right coronary artery and left anterior descending artery, and then TAVR was performed without complications. The patient tolerated the procedure well, with hemodynamics remaining stable throughout. At one-year follow-up, the patient's heart function was significantly improved. This case provides valuable experience in treating high-risk AS combined with CAD, demonstrating the feasibility and effectiveness of this approach in clinical practice.